Toward functional community engagement in academia: the Nigerian university experience - Adekalu, Samuel Olutokunbo; Suandi, Turiman; Krauss, Steven Eric; Ismail, Ismi Arif (Universiti Putra Malaysia Press, 2018)
Academics who choose to engage in community service to fulfil their internal professional obligations often face challenges that force them to turn to private consultancy work outside of their university obligations. This is often for better remuneration and personal fulfilment, rather than a perceived importance to scholarly engagement in service to the immediate community. Although much research has been conducted on community engagement in higher education, few studies have explored how such work is sustained, especially among academics in non-Western universities. In response, this study sets out to explore sustainable community engagement among academics in Nigeria, where academic community engagement has recently been given a renewed emphasis by policy makers. The study utilized a qualitative case study approach, by way of in-depth interviews with nine professors from diverse academic fields of study in a community-based Nigerian university. The findings point to several potential strategies for making community engagement more sustainable, including incorporating community engagement into university policies, providing a more supportive institutional culture, facilitating engagement through reward and recognition of engaging academics, conducting continuous research into community problems, and encouraging engagement based on academics’ area of specialization. Implications to practice and suggestions for future research are also presented.